High-strength foam light soil and preparation method thereof
By using fly ash, aluminium tailings slag and composite reinforcement materials in foam light soil, combined with electrophoretic deposition method to enhance hollow carbon fiber, the problem of uneven settlement of foam light soil under vibration is solved, and its compressive strength is improved and stability ensures the safety and service life of bridges and high-fill sections.
Patent Information
- Application Number
- CN202411229294.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-24
AI Technical Summary
Traditional foam light soil is prone to uneven settlement due to its own strength reasons under the influence of vibration, which affects the stability and safety of bridges and high-fill sections.
The preparation method of high-strength foam light soil is used to improve the compressive strength and stability of foam light soil by using fly ash, aluminium tailings slag and composite reinforcement materials such as hollow carbon fiber and hollow glass microspheres, combined with Electrophoretic deposition method enhances the surface properties of hollow carbon fibers and forms modified hollow carbon fibers to improve the mechanical properties of the material.
It significantly improves the compressive strength and stability of foam light soil, reduces constant load and soil pressure, enhances structural safety after filling, avoids uneven settlement, and extends service life.
Smart Images

Figure BDA0005025607930000071 
Figure BDA0005025607930000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of road and bridge construction, and more specifically, to a high-strength foamed lightweight soil and a preparation method thereof. Background Art
[0002] Foamed lightweight soil is a finished product made by air bubble mixed lightweight soil equipment. It is a new type of lightweight thermal insulation material containing a large number of closed pores. It has the characteristics of lightness, integrity, independence and easy construction. It has high fluidity, can be pumped over long distances, has a large construction surface and can be poured vertically. Therefore, it is widely used in backfill, field, highway roadbed, bridge abutment backfill and other projects to reduce dead load and soil pressure and improve the safety and service life of engineering structures.
[0003] With the development of public transportation, the geomorphic units in some construction areas are complex and the terrain is undulating. When building public roads, there are many bridges along the line, and a large amount of high fill and bridgehead roadbed construction is required. The traditional earth and stone backfill settlement deformation is large, which is not conducive to the safe operation of the road. Therefore, a large amount of foam lightweight soil is used to replace earth and stone for bridgehead roadbed and high fill sections. However, in actual use, under the influence of vibration, foam lightweight soil is prone to uneven settlement due to its own strength. Summary of the invention
[0004] In order to improve the strength of foamed lightweight soil, the present application provides a high-strength foamed lightweight soil and a preparation method thereof.
[0005] In the first aspect, the present application provides a high-strength foamed lightweight soil, which adopts the following technical solution: A high-strength foamed lightweight soil comprises the following raw materials in parts by weight: 40-85 parts of cement, 15-18 parts of fly ash, 2-7 parts of aluminum ore tailings slag, 0.2-0.5 parts of composite reinforcing material, 20-25 parts of water and 500-550L / m 3 Foam.
[0006] By adopting the above technical scheme, a small amount of fly ash can improve the sulfate resistance and chemical corrosion resistance of cement, and can also act as an aluminum correction substance. Bauxite tailings slag contains more aluminum oxide and part of iron oxide. The use of bauxite tailings slag to partially replace fly ash can not only supplement aluminum oxide but also serve as an iron correction substance. The addition of foam can make the material lighter and reduce the dead load and soil pressure, while the composite reinforcing material can enhance the strength of the foam lightweight soil, thereby improving the stability of the foam lightweight soil after filling.
[0007] Preferably, the composite reinforcement material comprises hollow carbon fibers and hollow glass microspheres in a mass ratio of (0.8-1.2):(0.6-0.9).
[0008] By adopting the above technical scheme, the addition of hollow carbon fibers and hollow glass microspheres can effectively improve the compressive strength of foam lightweight soil. By controlling the addition amount of hollow carbon fibers and hollow glass microspheres, the hollow carbon fibers and hollow glass microspheres are not easy to agglomerate and can be evenly dispersed in the foam lightweight soil, so that the hollow carbon fibers and hollow glass microspheres can effectively improve the compressive strength of the foam lightweight soil.
[0009] Preferably, the method for preparing the hollow carbon fiber comprises the following steps: dissolving polyacrylonitrile powder in N,N-dimethylformamide, stirring evenly at 60-65°C to obtain a shell spinning solution, dissolving polymethyl methacrylate in N,N-dimethylformamide to obtain a core spinning solution, coaxially electrospinning the shell spinning solution and the core spinning solution to form a composite fiber, and carbonizing the composite fiber after pre-oxidation to obtain a hollow carbon fiber.
[0010] By adopting the above technical scheme, polymethyl methacrylate fiber is used as the inner layer of the composite fiber, so that the polyacrylonitrile fiber of the outer layer forms a hollow fiber structure. After high-temperature carbonization, the polymethyl methacrylate fiber is decomposed at high temperature, and the polyacrylonitrile fiber is carbonized at high temperature to form a carbon fiber with a hollow structure, thereby obtaining a hollow carbon fiber.
[0011] Preferably, the ratio of the extrusion rate of the core layer spinning solution to the shell layer spinning solution is 1:(0.32-0.36).
[0012] By adopting the above technical scheme and controlling the extrusion rates of the core layer spinning solution and the shell layer spinning solution, the diameter and thickness of the composite fiber shell layer and the core layer can be effectively controlled, thereby effectively controlling the diameter and size of the hollow carbon fibers, so that the prepared hollow carbon fibers have good mechanical properties and ensure the compressive strength of the foam lightweight soil.
[0013] Preferably, the hollow carbon fibers are post-treated as follows: graphene oxide is ultrasonically dispersed in water to form a suspension, hollow carbon fibers are added and ultrasonically dispersed in the suspension, sodium hydroxide solution is added to adjust the pH to 10-10.5, and then electrophoretic deposition is performed, centrifuged, and dried to obtain modified hollow carbon fibers.
[0014] By adopting the above technical scheme, after the hollow carbon fibers are placed in a suspension, electrophoretic deposition is performed to graft graphene oxide onto the surface of the hollow carbon fibers, and the surface of the modified hollow carbon fibers becomes rougher, so that the bonding effect in the foam lightweight soil is better. When the foam lightweight soil is subjected to stress, the modified hollow carbon fibers have a better effect of transmitting the stress, thereby improving the compressive strength of the foam lightweight soil.
[0015] Preferably, the mass ratio of the hollow carbon fiber, graphene oxide and water is (1.5-1.8):(0.18-0.22):(46-52).
[0016] By adopting the above technical scheme and controlling the mass ratio of hollow carbon fibers, graphene oxide and water, the concentration of graphene oxide in the graphene oxide suspension can be effectively controlled, thereby making the electrophoretic deposition effect of graphene oxide on the surface of hollow carbon fibers better, and graphene oxide can be better grafted on the surface of hollow carbon fibers.
[0017] Preferably, the graphene oxide is modified graphene oxide with carbon nanotubes grown on the surface.
[0018] By adopting the above technical scheme, carbon nanotubes grow on the surface of graphene oxide. The carbon nanotubes have excellent mechanical properties. The graphene oxide coated with carbon nanotubes has a stronger effect on enhancing the strength of foam lightweight soil. After the foam lightweight soil is subjected to force, the carbon nanotubes can enhance the mechanical properties of graphene oxide, thereby improving the compressive strength of the foam lightweight soil.
[0019] In a second aspect, the present application provides a method for preparing high-strength foamed lightweight soil, using the following technical solution: A method for preparing high-strength foamed lightweight soil, comprising the following steps: The composite reinforcement material is added into water and ultrasonically dispersed to obtain a uniform suspension; cement, fly ash and diatomite tailings slag are fully mixed, added into the suspension and stirred until the mixture is uniform, and then foam is added and stirred until the mixture is uniform to obtain foam lightweight soil slurry, which is filled into a mold, left to stand and demolded, and then cured to obtain foam lightweight soil.
[0020] By adopting the above technical solution, hollow carbon fibers and hollow glass microspheres are dispersed in water. When water is mixed with solid raw materials, it helps to evenly disperse the hollow carbon fibers and hollow glass microspheres in the foam lightweight soil slurry.
[0021] In summary, this application has the following beneficial effects: 1. Since the present application adopts fly ash and diatomite tailings slag, it can improve the sulfate resistance and chemical corrosion resistance of cement, and can also serve as the source and correction material of aluminum and iron elements. The addition of foam can make the foam lightweight soil lighter, and when used for backfilling, it can effectively reduce the dead load and soil pressure. The composite reinforcement material can improve the compressive strength of the foam lightweight soil, thereby improving the stability of the foam lightweight soil.
[0022] 2. In this application, hollow carbon fibers and hollow glass microspheres are preferably used as composite reinforcing materials. Hollow glass microspheres have good tensile strength, compressive strength, etc., and hollow carbon fibers have good mechanical properties. Adding hollow carbon fibers and hollow glass microspheres is beneficial to improving the compressive strength and mechanical strength of the foam lightweight soil. The fibrous structure of the hollow carbon fibers and the spherical structure of the hollow glass microspheres, and their different forms can fill the gaps in the foam lightweight soil, thereby improving the compressive strength of the foam lightweight soil.
[0023] 3. In this application, graphene oxide is grafted onto the surface of hollow carbon fibers by electrophoretic deposition method. The surface of the modified hollow carbon fibers is rougher, which is beneficial to the close combination of the modified hollow carbon fibers and other raw materials, and is beneficial to the conduction effect of stress when the foam lightweight soil is subjected to stress, thereby improving the compressive strength of the foam lightweight soil. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with embodiments.
[0025] Preparation Example 1-11 of Hollow Carbon Fiber Preparation Example 1 Polyacrylonitrile powder was dissolved in N,N-dimethylformamide and stirred evenly at 60°C to obtain a shell spinning solution with a concentration of 7wt%. Polymethyl methacrylate was dissolved in N,N-dimethylformamide to obtain a core spinning solution with a concentration of 31wt%. The shell spinning solution and the core spinning solution were coaxially electrospun to form composite fibers. The composite fibers were pre-oxidized and then carbonized to obtain hollow carbon fibers. The spinning voltage of the coaxial electrospinning was 22kV, the extrusion rate of the core spinning solution was 9mL / h, the extrusion rate of the shell spinning solution was 2.88mL / h, and the receiving distance was 22cm.
[0026] Preparation Example 2 Polyacrylonitrile powder was dissolved in N,N-dimethylformamide and stirred evenly at 65°C to obtain a shell spinning solution with a concentration of 9wt%. Polymethyl methacrylate was dissolved in N,N-dimethylformamide to obtain a core spinning solution with a concentration of 34wt%. The shell spinning solution and the core spinning solution were coaxially electrospun to form composite fibers. The composite fibers were pre-oxidized and then carbonized to obtain hollow carbon fibers. The spinning voltage of the coaxial electrospinning was 23kV, the extrusion rate of the core spinning solution was 9mL / h, the extrusion rate of the shell spinning solution was 3.24mL / h, and the receiving distance was 24cm.
[0027] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the extrusion rate of the core layer spinning solution is 9 mL / h, and the extrusion rate of the shell layer spinning solution is 2 mL / h.
[0028] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the extrusion rate of the core layer spinning solution is 9 mL / h, and the extrusion rate of the shell layer spinning solution is 4 mL / h.
[0029] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that the hollow carbon fiber is also subjected to the following post-treatment: 0.12 g of graphene oxide is ultrasonically dispersed in 30.67 mL of water to form a suspension, 1 g of hollow carbon fiber is added and ultrasonically dispersed in the suspension, 10 wt % sodium hydroxide solution is added to adjust the pH to 10, and then the electrophoretic deposition method is used. The distance between the two electrodes is 1 cm, the operating voltage is 30 kV, and the operating time is 1 h. After electrophoretic deposition, centrifugation, and drying, the modified hollow carbon fiber is obtained.
[0030] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that the hollow carbon fiber is also subjected to the following post-treatment: 0.15 g of graphene oxide is ultrasonically dispersed in 34.67 mL of water to form a suspension, 1.2 g of hollow carbon fiber is added and ultrasonically dispersed in the suspension, 10 wt % sodium hydroxide solution is added to adjust the pH to 10.5, and then the electrophoretic deposition method is used. The distance between the two electrodes is 1 cm, the operating voltage is 30 kV, and the operating time is 1 h. After electrophoretic deposition, centrifugation, and drying, the modified hollow carbon fiber is obtained.
[0031] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 5 is that the amount of graphene oxide added in Preparation Example 7 is 0.05 g.
[0032] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 5 is that the amount of graphene oxide added in Preparation Example 8 is 0.2 g.
[0033] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 5 is that the added amount of the hollow carbon fiber in Preparation Example 9 is 0.5 g.
[0034] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 5 is that the added amount of the hollow carbon fiber in Preparation Example 10 is 1.5 g.
[0035] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 5 is that the graphene oxide is modified graphene oxide with carbon nanotubes grown on the surface, and the preparation method of the modified graphene oxide comprises the following steps: 480 mg of graphene oxide was ultrasonically dispersed in 500 ml of ethanol solution, wherein the volume ratio of ethanol to water in the ethanol solution was 9:1. 10 wt % ammonia water was then added to adjust the pH to 9, and 1 mL of tetraethoxysilane was added. After reacting for 16 h, the centrifuged product was obtained after centrifugal washing and transferred to a tube furnace. After argon was introduced and the temperature was raised to 600 ° C, a xylene solution of ferrocene with a concentration of 0.05 mg / mL was introduced, and after reacting for 5 min, acetylene was introduced and reacted for 10 min to obtain graphene oxide with carbon nanotubes coated on the surface. Example
[0036] The cement selected in the embodiments and comparative examples of the present application is P·O42.5 silicate cement, the fly ash is commercially available Class I fly ash, and its specifications meet the requirements of "Fly Ash Used in Cement and Concrete" (GBT1596-2017); the diatomite tailings slag is the waste slag of bauxite tailings from Hejin City, Shanxi Province, with a mass fraction of Al2O3 of 45%, a mass fraction of Fe2O3 of 8%, and a mass fraction of TiO2 of 0.1%.
[0037] Example 1 A high-strength foamed lightweight soil comprises the following raw materials in parts by weight: 40 kg of cement, 15 kg of fly ash, 2 kg of aluminum tailings slag, 0.2 kg of composite reinforcing material, 20 kg of water and 500 L / m 3 The foam is prepared by mixing the composite reinforcing material with the hollow carbon fibers and the hollow glass microspheres in a mass ratio of 0.8:0.6. The hollow carbon fibers are the hollow carbon fibers prepared in Preparation Example 1, and the hollow glass microspheres are HGS2000.
[0038] The preparation method of the high-strength foamed lightweight soil comprises the following steps: adding the composite reinforcement material to water, and ultrasonically dispersing for 25 minutes to obtain a uniform suspension; fully mixing cement, fly ash, and diaspore tailings slag, adding the suspension and continuing to stir until the mixture is uniform, adding foam and continuing to stir until the mixture is uniform, to obtain foamed lightweight soil slurry, filling the slurry into a mold, placing the slurry at room temperature for 48 hours, demolding the slurry, and curing the slurry for 28 days to obtain foamed lightweight soil.
[0039] Example 2 A high-strength foamed lightweight soil comprises the following raw materials in parts by weight: 85 kg of cement, 18 kg of fly ash, 7 kg of aluminum ore tailings slag, 0.5 kg of composite reinforcing material, 25 kg of water and 550 L / m 3 Foam, wherein the composite reinforcement material includes hollow carbon fibers and hollow glass microspheres in a mass ratio of 1.2:0.9, the hollow carbon fibers are the hollow carbon fibers prepared in Preparation Example 2, and the hollow glass microspheres are HGS3000.
[0040] The preparation method of the high-strength foamed lightweight soil comprises the following steps: adding the composite reinforcement material to water, and ultrasonically dispersing for 30 minutes to obtain a uniform suspension; fully mixing cement, fly ash, and diaspore tailings slag, adding the suspension and continuing to stir until the mixture is uniform, adding foam and continuing to stir until the mixture is uniform, to obtain foamed lightweight soil slurry, filling the slurry into a mold, placing the slurry at room temperature for 48 hours, demolding the slurry, and curing the slurry for 28 days to obtain foamed lightweight soil.
[0041] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the hollow carbon fibers in the composite reinforcement material are the hollow carbon fibers prepared in Preparation Example 3.
[0042] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the hollow carbon fibers in the composite reinforcement material are hollow carbon fibers prepared in Preparation Example 4.
[0043] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the hollow carbon fibers in the composite reinforcement material are the hollow carbon fibers prepared in Preparation Example 5.
[0044] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the hollow carbon fibers in the composite reinforcement material are hollow carbon fibers prepared in Preparation Example 6.
[0045] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the hollow carbon fibers in the composite reinforcement material are the hollow carbon fibers prepared in Preparation Example 7.
[0046] Example 8 The difference between Example 8 and Example 1 is that in Example 7, the hollow carbon fibers in the composite reinforcement material are the hollow carbon fibers prepared in Preparation Example 8.
[0047] Example 9 The difference between Example 9 and Example 1 is that in Example 9, the hollow carbon fibers in the composite reinforcement material are hollow carbon fibers prepared in Preparation Example 9.
[0048] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the hollow carbon fibers in the composite reinforcement material are the hollow carbon fibers prepared in Preparation Example 10.
[0049] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the hollow carbon fibers in the composite reinforcement material are hollow carbon fibers prepared in Preparation Example 11.
[0050] Example 12 The difference between Example 12 and Example 1 is that in Example 12, the composite reinforcement material includes hollow carbon fibers and hollow glass microspheres in a mass ratio of 0.8:0.3.
[0051] Example 13 The difference between Example 13 and Example 1 is that in Example 13, the composite reinforcement material includes hollow carbon fibers and hollow glass microspheres in a mass ratio of 0.8:1.
[0052] Embodiment 14 The difference between Example 14 and Example 1 is that in Example 14, the composite reinforcement material is hollow carbon fiber.
[0053] Embodiment 15 The difference between Example 15 and Example 1 is that in Example 15, the composite reinforcement material is hollow glass microspheres.
[0054] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the following raw materials are included in weight: 60 kg cement, 10 kg fly ash, 15 kg diatomite tailings slag, 0.8 kg composite reinforcement material, 30 kg water and 450 L / m 3 The foam, wherein the composite reinforcement material comprises hollow carbon fibers and hollow glass microspheres in a mass ratio of 0.8:0.6, the hollow carbon fibers are the hollow carbon fibers prepared in Preparation Example 1, and the hollow glass microspheres are HGS2000.
[0055] Comparative Example 2 The difference between the comparative example and the embodiment 1 is that in the comparative example 2, no composite reinforcing material is added.
[0056] Detection Methods According to the raw materials and preparation methods of Examples 1-15 and Comparative Examples 1-2, foamed lightweight soil was obtained after 28 days of curing, and the dry density and compressive strength of the foamed lightweight soil were tested. The testing method was based on GB / T50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the results were recorded in Table 1.
[0057] Table 1 Density and compressive strength of foamed lightweight soil According to Table 1, Examples 1-2 and Comparative Examples 1-2, it can be seen that the foamed lightweight soil prepared in Examples 1-2 can have a higher compressive strength while maintaining a lower dry density. Comparative Example 1 adjusts the raw material composition of the foamed lightweight soil, indicating that compared with the raw material composition of Comparative Example 1, the foamed lightweight soil prepared by the raw materials and their weight parts in Examples 1-2 has better mechanical properties and higher compressive strength; no composite reinforcing material is added in Comparative Example 2, and the compressive strength of Comparative Example 2 is lower than that of Examples 1-2, indicating that the composite reinforcing material can maintain the foamed lightweight soil with a lower density and improve the compressive strength of the foamed lightweight soil, so that the foamed lightweight soil has good stability after filling and is not easily deformed or broken.
[0058] The density of foam lightweight soil is low, so when foam lightweight soil is used for backfill, it can effectively reduce the dead load and soil pressure, reduce the settlement of soil and rock in the bridgehead roadbed and high fill section, and at the same time, the addition of composite reinforcing materials can effectively improve the compressive strength of foam lightweight soil, so that the foam lightweight soil has good compressive strength while maintaining a low density and is not easy to deform, thereby improving the stability of the foam lightweight soil during use.
[0059] Compared with Example 1, the compressive strength of Example 3-4 is reduced. When preparing hollow carbon fibers, Example 3-4 changes the extrusion rate of the shell spinning solution. The extrusion rate of the shell spinning solution and the extrusion rate of the core spinning solution directly affect the size and mechanical properties of the hollow carbon fibers. The extrusion rate of the shell spinning solution is relatively low, which easily makes the shell layer of the composite fiber thinner, and the hollow carbon fiber structure formed after carbonization is unstable. The extrusion rate of the shell spinning solution is too high, which easily makes the diameter of the hollow carbon fibers after carbonization too large, and the formed morphology is poor. The mechanical properties and mechanical strength of the hollow carbon fibers are reduced, thereby affecting the compressive strength of the foam lightweight soil.
[0060] Compared with Example 1, the compressive strength of Example 5-6 is increased. When preparing hollow carbon fibers, graphene oxide is grafted on the surface of the hollow carbon fibers by electrophoretic deposition. The surface of the grafted hollow carbon fibers is rougher, which is conducive to better bonding between the modified hollow carbon fibers and the foam lightweight soil. When the foam lightweight soil is subjected to stress, the modified hollow carbon fibers are tightly bonded to the foam lightweight soil, and the stress conduction effect is better, which can further improve the compressive strength of the foam lightweight soil.
[0061] Compared with Example 5, the compressive strength of Example 7-8 is reduced. When preparing hollow carbon fibers, Example 7-8 adjusts the amount of graphene oxide added during the electrophoretic deposition process, indicating that the content of graphene oxide in the suspension affects the grafting of graphene oxide on the surface of the hollow carbon fibers, thereby affecting the performance of the modified hollow carbon fibers. When the amount of graphene oxide added is too high, the graphene oxide in the suspension is prone to agglomeration, thereby affecting the uniform dispersion of graphene oxide and affecting the contact and grafting of graphene oxide with the hollow carbon fibers. When the amount of graphene oxide added is too little, the grafting rate of graphene oxide on the hollow carbon fibers decreases, thereby reducing the performance of the modified hollow carbon fibers.
[0062] Compared with Example 5, the compressive strength of Example 9-10 is reduced. When preparing hollow carbon fibers, Example 9-10 adjusted the amount of hollow carbon fibers added, indicating that the mass ratio of hollow carbon fibers to graphene oxide will affect the grafting of graphene oxide on the surface of hollow carbon fibers. When the amount of hollow carbon fibers added is too little and the amount of graphene oxide is too much, more graphene oxide is attached to the surface of the hollow carbon fibers, and the grafting effect is poor. When the amount of hollow carbon fibers added is too much and the amount of graphene oxide is too little, the amount of graphene oxide grafted on the surface of the modified hollow carbon fibers is less, thereby reducing the performance of the modified hollow carbon fibers.
[0063] Compared with Example 5, the compressive strength of Example 11 is increased. When preparing hollow carbon fibers, Example 11 uses modified graphene oxide with carbon nanotubes grown on the surface. The carbon nanotubes have good mechanical properties. The graphene oxide coated with carbon nanotubes has a better effect on enhancing the mechanical properties of the foamed lightweight soil, thereby improving the compressive strength of the foamed lightweight soil.
[0064] Compared with Example 1, the compressive strength of Example 12-13 is reduced. The mass ratio of hollow carbon fibers and hollow glass microspheres in the composite reinforcing material is adjusted in Example 12-13, indicating that the mass ratio of hollow carbon fibers and hollow glass microspheres has an impact on the reinforcement effect of foam lightweight soil. When the addition amount of hollow carbon fibers and hollow glass microspheres is too much, agglomeration is prone to occur. Moreover, the morphological structures of hollow carbon fibers and hollow glass microspheres are different, which can fill different gaps in the foam lightweight soil to form a continuous stress conduction structure, thereby effectively improving the compressive strength of the foam lightweight soil.
[0065] Compared with Example 1, the compressive strength of Examples 14-15 is reduced. In Example 14, only hollow carbon fibers are added as composite reinforcement materials, while in Example 15, only hollow glass microspheres are added as composite reinforcement materials. This indicates that the composite reinforcement material formed by the hollow carbon fibers and hollow glass microspheres has a better reinforcement effect on the foam lightweight soil, and the obtained foam lightweight soil has higher compressive strength.
[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A high-strength foamed lightweight soil, characterized in that: The raw materials include the following parts by weight: 40-85 parts of cement, 15-18 parts of fly ash, 2-7 parts of aluminum tailings slag, 0.2-0.5 parts of composite reinforcement material, 20-25 parts of water and 500-550L / m 3 Foam.
2. The high-strength foamed lightweight soil according to claim 1, characterized in that: The composite reinforcement material comprises hollow carbon fibers and hollow glass microspheres in a mass ratio of (0.8-1.2):(0.6-0.9).
3. The high-strength foamed lightweight soil according to claim 2, characterized in that: The preparation method of the hollow carbon fiber comprises the following steps: dissolving polyacrylonitrile powder in N,N-dimethylformamide, stirring evenly at 60-65°C to obtain a shell spinning solution, dissolving polymethyl methacrylate in N,N-dimethylformamide to obtain a core spinning solution, coaxially electrospinning the shell spinning solution and the core spinning solution to form a composite fiber, and carbonizing the composite fiber after pre-oxidation to obtain the hollow carbon fiber.
4. The high-strength foamed lightweight soil according to claim 3, characterized in that: The ratio of the extrusion rate of the core layer spinning solution to the shell layer spinning solution is 1:(0.32-0.36).
5. The high-strength foamed lightweight soil according to claim 2, characterized in that: The hollow carbon fibers are post-treated as follows: graphene oxide is ultrasonically dispersed in water to form a suspension, hollow carbon fibers are added and ultrasonically dispersed in the suspension, sodium hydroxide solution is added to adjust the pH to 10-10.5, and then electrophoretic deposition is performed, centrifuged, and dried to obtain modified hollow carbon fibers.
6. The high-strength foamed lightweight soil according to claim 5, characterized in that: The mass ratio of the hollow carbon fiber, graphene oxide and water is (1.5-1.8):(0.18-0.22):(46-52).
7. The high-strength foamed lightweight soil according to claim 5, characterized in that: The graphene oxide is modified graphene oxide with carbon nanotubes grown on the surface.
8. The method for preparing a high-strength foamed lightweight soil according to any one of claims 1 to 7, characterized in that: The following steps are involved: The composite reinforcement material is added into water and ultrasonically dispersed to obtain a uniform suspension; cement, fly ash and diatomite tailings slag are fully mixed, added into the suspension and stirred until the mixture is uniform, and then foam is added and stirred until the mixture is uniform to obtain foam lightweight soil slurry, which is filled into a mold, left to stand and demolded, and then cured to obtain foam lightweight soil.
